Pleasant touch perception in borderline personality disorder and its relationship with disturbed body representation - Löffler, Annette; Kleindienst, Nikolaus; Neukel, Corinne; Bekrater-Bodmann, Robin; Flor, Herta (Borderline Personality Disorder and Emotion Dysregulation, 2022)
Borderline personality disorder (BPD) is characterized by altered perception of affective stimuli, including abnormal evaluation of nociceptive input. However, whether or not perceptual alterations are present for its positive counterpart, i.e. pleasant touch (PT), has not yet been examined.